Predictive value of biliverdin reductase‐A and homeostasis model assessment of insulin resistance on mild cognitive impairment in patients with type 2 diabetes - Li Shen; Xiaole Wei; Nan Wang; Haorui Lv; Jing Huang; Xiaoyan Zhou; Aifang Cheng; Changjiang Ying (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction To investigate the predictive value of the biliverdin reductase‐A (BVR‐A) and the homeostasis model assessment for insulin resistance (HOMA‐IR) on mild cognitive impairment (MCI) in patients with type 2 diabetes mellitus, and to establish a nomogram model. Materials and Methods This study included 140 patients with type 2 diabetes mellitus. Based on Montreal Cognitive Assessment (MoCA) scores, participants were categorized into the normal cognitive function (T2DM‐NCF) group (65 cases) and the mild cognitive impairment (T2DM‐MCI) group (75 cases). Multivariate logistic regression analysis was performed to identify the factors associated with MCI in patients with type 2 diabetes mellitus. A nomogram prediction model was developed using R software for the selected factors, and its predictability and accuracy were verified. Results Compared with the T2DM‐NCF group, subjects with MCI were older, had a longer duration of diabetes, higher HOMA‐IR, lower BVR‐A, lower cognitive scores, and lower education levels (all P < 0.05). Multivariate logistic regression analysis showed that duration of diabetes (OR = 1.407, 95% CI: 1.163–1.701), HOMA‐IR (OR = 1.741, 95% CI: 1.197–2.53), and BVR‐A (OR = 0.528, 95% CI: 0.392–0.712) were significantly associated with the development of MCI in patients with type 2 diabetes mellitus. The C‐index of the nomogram was 0.863 (95% CI: 0.752–0.937). Conclusions Our findings suggest that BVR‐A and HOMA‐IR are significantly associated with the development of MCI in patients with type 2 diabetes mellitus. The nomogram incorporating BVR‐A and HOMA‐IR aids in predicting the risk of developing MCI in these patients.